Synthesis and Characterization of pH Stimuli-Responsive Mesoporous Silica Nanoparticles - Lavilla Gomez, Maria del Carmen (2017)
In the field of bionanotechnology, the interest in the development of healthcare devices has increased due to their applications on diagnostics and therapeutics. Mesoporous silica nanoparticles (MSNs) have been used in drug delivery systems (DDSs) as nanocarriers due their excellent biocompatibility, high surface areas, large pore volumes, high payload, uniform and tunable pore sizes, and versatile of surface functionalization. The incorporation of a stimuli-responsive polymeric shell allows the drug release control response through a disease-specific physiological conditions, and/or from external applied stimuli. Additionally, it will protect the therapeutic molecules from physiological metabolization and enhance its efficiency and bioavailability in the bloodstream, as well as reduce the side effects. The goal of this work was to prepare a fluorescent core-shell MSNs, coated with a pH-responsive polymeric shell, combining diagnostic and therapeutic properties in a single vector. Reversible Addition-Fragmentation Chain Transfer (RAFT) polymerization was used to obtain a homogeneous polymeric shell with a well-defined structure. The hybrid nanoparticles were characterized by Transmission Electronic Microscopy (TEM) and Dynamic Light Scattering (DLS), allowing diameters around 150 nm. The polymeric shell was characterized by Proton Nuclear Magnetic Resonance spectroscopy (1H NMR), Fourier Transform Infrared Spectroscopy (FT-IR) and electrophoretic mobility (ζ-potential). The pH responsive behavior was proven by ζ-Potential with an estimated conformational transition at pH between 6.2 – 6.5. The hybrid nanoparticles indicate being biocompatible tested by cell viability assays in human breast adenocarcinoma (MCF-7), which showed that for a concentration of 125 μg/mL the cell viability is over 70 %.